Parental depression and child temperament: assessing child to parent effects in a longitudinal population study. - Hanington, L; Ramchandani, P; Stein, A (2010)
Current research supports a link between maternal depression and difficult child temperament. The direction of effect is often assumed to be from parent to child, but few studies have addressed child to parent effects. In a large cohort study, the Avon Longitudinal Study of Parents and Children (ALSPAC) (N=14663), we aimed to further existing knowledge by investigating the relationship between maternal and paternal depressive symptoms and child temperament, and determining the direction of any effects found. Data was collected at 2 time-points (when the children were 6 and 24 months old), using the Edinburgh Postnatal Depression Scale and the Mood and Intensity subscales of the Carey Temperament Scales. Significant parent to child effects were seen, with maternal and paternal depressive symptoms at Time 1 leading to more difficult temperament at Time 2. Father to child effects were significant only in male children. Little evidence was found for child to parent effects.